2020
DOI: 10.2340/00015555-3638
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Skin Microbiome Associated with Change in Skin Status in Patients with Psoriasis

Abstract: The aim of this study was to identify key microbes associated with change in skin status (lesional vs normal). Longitudinal changes in the skin microbiome between patients with psoriasis and healthy family controls living in the same household were studied using whole genome metagenomic shotgun sequencing at 4 time-points. There were significant changes in abundance of the pathogen Campylobacter jejuni and its higher taxonomic levels when the skin status of patients with psoriasis change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…The results of skin microbiome studies in patients with psoriasis are not fully consistent [ 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Studies by Alekseyenko et al, Wang et al, and Langan et al showed that the biodiversity in psoriatic lesions is reduced compared to healthy skin [ 97 , 98 , 99 ]. A study by Chang et al found increased biodiversity in skin affected by psoriasis, while a study by Fahlen et al found no difference [ 100 , 101 ].…”
Section: Skin Microbiome In Patients With Psoriasismentioning
confidence: 99%
See 2 more Smart Citations
“…The results of skin microbiome studies in patients with psoriasis are not fully consistent [ 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Studies by Alekseyenko et al, Wang et al, and Langan et al showed that the biodiversity in psoriatic lesions is reduced compared to healthy skin [ 97 , 98 , 99 ]. A study by Chang et al found increased biodiversity in skin affected by psoriasis, while a study by Fahlen et al found no difference [ 100 , 101 ].…”
Section: Skin Microbiome In Patients With Psoriasismentioning
confidence: 99%
“…A study by Chang et al found increased biodiversity in skin affected by psoriasis, while a study by Fahlen et al found no difference [ 100 , 101 ]. The most abundant bacteria harboring psoriatic lesions are the bacteria of the Firmicutes phylum which are present on psoriatic skin in a larger proportion than on the skin of healthy subjects [ 101 , 102 ], whereas the phyla Actinobacteria [ 98 , 99 , 100 , 101 , 102 ] and Proteobacteria are reduced [ 102 ]. Aside from that, studies show an increase in the abundance of Streptococcus [ 102 ] and Staphylococcus genera [ 6 , 99 ], i.e., certain species of Staphylococcus aureus , Staphylococcus pettenkoferi, and Staphylococcus sciuri , and the depletion of the genus Cutibacterium , Staphylococcus epidermidis , Cutibacterium acnes, and Cutibacterium granulosum species [ 100 , 102 ].…”
Section: Skin Microbiome In Patients With Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 20 selected studies, three studies are focussed on fungal microbiota, 16,26,27 1 on bacteriophage community, 37 13 on bacterial 15,[21][22][23][24][25][30][31][32][33][34]36,38 and 3 on whole microbial community including fungus, bacteriophage and bacteria. 28,29,35 The variable regions of 16S rRNA such as V1-V3 or V3-V5 are very important to define the diversity of microbial community in samples. Most of the studies have targeted V1-V3 or V3-V5 for sequencing and identify the diversity at different taxa levels in skin samples (Table 2).…”
Section: Methodologies Incorporated To Measure Microbiota Of Lesional...mentioning
confidence: 99%
“…Moreover, significant abundance of Campylobacter jejuni pathogen has been reported from lesional psoriatic skin. 28 In addition, Xanthomonas (Keratolytic) and Corynebacterium genera are associated with lesional psoriatic skin according to the report by Martin et al 33 From a recent study, Capnocytophaga, Leptotrichia, Abiotrophia and Tannerella are known to play an important role in the severity of lesional psoriatic skin. 30 In another report, Prevotella and Staphylococcus were suggested to have association with lesional psoriatic skin whereas Anaerococcus and Propionibacterium with normal skin.…”
Section: Skin Microbiota Inhabiting the Lesional Psoriatic Skinmentioning
confidence: 97%